Corrigendum to ‘Comparison of two pump-based systems for sampling small microplastics (>10 μM) in coastal waters’ [Environmental Pollution 363-P2 (2024) 125192] - Kevin Ugwu; Alvise Vianello; Rodrigo Almeda; Lucian Iordachescu; Anna Rotander (Environmental Pollution, 2025)

Comparison of two pump-based systems for sampling small microplastics (>10 μM) in coastal waters - Kevin Ugwu; Alvise Vianello; Rodrigo Almeda; Lucian Iordachescu; Anna Rotander (Environmental Pollution, 2024)

Metabolic changes associated with PFAS exposure in firefighters: A pilot study - Anna Rotander; Maria Jose Gomez Ramos; Jochen F. Mueller; Leisa-Maree Toms; Tuulia Hyötyläinen (Science of The Total Environment, 2024)

New insights into the impact of leachates from in-field collected plastics on aquatic invertebrates and vertebrates - Chiara Gambardella; Roberta Miroglio; Elisa Costa; Jérôme Cachot; Bénédicte Morin; Christelle Clérandeau; Anna Rotander; Kevin Rocco; Giuseppe d’Errico; Rodrigo Almeda; Olalla Alonso; Etienne Grau; et al. (Environmental Pollution, 2024)

A case study on microlitter and chemical contaminants: Assessing biological effects in the southern coast of the Gulf of Finland (Baltic sea) using the mussel Mytilus trossulus as a bioindicator - Ivan Kuprijanov; Natalja Buhhalko; Ulrika Eriksson; Viktor Sjöberg; Anna Rotander; Natalja Kolesova; Maarja Lipp; Fred Buschmann; Arslan Hashmi; Taavi Liblik; Kari K. Lehtonen (Marine Environmental Research, 2024)

Looking beyond the obvious: The ecotoxicological impact of the leachate from fishing nets and cables in the marine mussel Mytilus galloprovincialis - Juliano M. Vilke; Tainá G. Fonseca; Gilberto D. Alkimin; Joanna M. Gonçalves; Carlos Edo; Giuseppe d’ Errico; Fredric Södergren Seilitz; Anna Rotander; Maura Benedetti; Francesco Regoli; Karim H. Lüchmann; Maria João Bebianno (Journal of Hazardous Materials, 2024)

Cocktail effects of tire wear particles leachates on diverse biological models: A multilevel analysis - Jessy Le Du-Carrée; Clara Kempkens Palacios; Anna Rotander; Maria Larsson; Andi Alijagic; Oleksandr Kotlyar; Magnus Engwall; Viktor Sjöberg; Steffen H. Keiter; Rodrigo Almeda (Journal of Hazardous Materials, 2024)

Comparison between manta trawl and in situ pump filtration methods, and guidance for visual identification of microplastics in surface waters - Therese M. Karlsson; Anna Kärrman; Anna Rotander; Martin Hassellöv (Environmental Science and Pollution Research, 2020)
Owing to the development and adoption of a variety of methods for sampling and identifying microplastics, there is now data showing the presence of microplastics in surface waters from all over the world. The difference between the methods, however, hampers comparisons, and to date, most studies are qualitative rather than quantitative. In order to allow for a quantitative comparison of microplastics abundance, it is crucial to understand the differences between sampling methods. Therefore, a manta trawl and an in situ filtering pump were compared during realistic, but controlled, field tests. Identical microplastic analyses of all replicates allowed the differences between the methods with respect to (1) precision, (2) concentrations, and (3) composition to be assessed. The results show that the pump gave higher accuracy with respect to volume than the trawl. The trawl, however, sampled higher concentrations, which appeared to be due to a more efficient sampling of particles on the sea surface microlayer, such as expanded polystyrene and air-filled microspheres. The trawl also sampled a higher volume, which decreased statistical counting uncertainties. A key finding in this study was that, regardless of sampling method, it is critical that a sufficiently high volume is sampled to provide enough particles for statistical evaluation. Due to the patchiness of this type of contaminant, our data indicate that a minimum of 26 particles per sample should be recorded to allow for concentration comparisons and to avoid false null values. The necessary amount of replicates to detect temporal or spatial differences is also discussed. For compositional differences and size distributions, even higher particle counts would be necessary. Quantitative measurements and comparisons would also require an unbiased approach towards both visual and spectroscopic identification. To facilitate the development of such methods, a visual protocol that can be further developed to fit different needs is introduced and discussed. Some of the challenges encountered while using FTIR microspectroscopic particle identification are also critically discussed in relation to specific compositions found.

Chemical and bioanalytical characterisation of PAHs in risk assessment of remediated PAH-contaminated soils - Maria Larsson; Jessika Hagberg; Anna Rotander; Bert van Bavel; Magnus Engwall (Environmental Science and Pollution Research, 2013)

Perfluoroalkyl substances (PFASs) in food and water from Faroe Islands - Ulrika Eriksson; Anna Kärrman; Anna Rotander; Bjørg Mikkelsen; Maria Dam (Environmental Science and Pollution Research, 2013)

AhR agonist and genotoxicant bioavailability in a PAH-contaminated soil undergoing biological treatment - Erika Andersson; Anna Rotander; Thomas von Kronhelm; Anna Berggren; Per Ivarsson; Henner Hollert; Magnus Engwall (Environmental Science and Pollution Research, 2009)